2019
DOI: 10.1158/0008-5472.can-19-0789
|View full text |Cite
|
Sign up to set email alerts
|

tRNA Fragments Show Intertwining with mRNAs of Specific Repeat Content and Have Links to Disparities

Abstract: tRNA-derived fragments (tRF) are a class of potent regulatory RNAs. We mined the datasets from The Cancer Genome Atlas (TCGA) representing 32 cancer types with a deterministic and exhaustive pipeline for tRNA fragments. We found that mitochondrial tRNAs contribute disproportionally more tRFs than nuclear tRNAs. Through integrative analyses, we uncovered a multitude of statistically significant and contextdependent associations between the identified tRFs and mRNAs. In many of the 32 cancer types, these associa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
92
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 70 publications
(108 reference statements)
9
92
1
Order By: Relevance
“…At the same time, and in addition to the full-length rRNAs, the nuclear genome is riddled with numerous partial copies of rRNAs. This is in parallel to what we observed for tRFs [26,30,31,48]. However, unlike tRFs, the partial copies of the longer rRNAs such as 12S, 16S, 18S, and 28S that can be found on the genome are themselves long.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…At the same time, and in addition to the full-length rRNAs, the nuclear genome is riddled with numerous partial copies of rRNAs. This is in parallel to what we observed for tRFs [26,30,31,48]. However, unlike tRFs, the partial copies of the longer rRNAs such as 12S, 16S, 18S, and 28S that can be found on the genome are themselves long.…”
Section: Discussionsupporting
confidence: 86%
“…6). This tissue-dependence observation is something that we showed to be the case through two large-scale analyses of isomiRs [25] and tRFs [30]. And, a recent report in bioRχiv [53] showed evidence that the aggregate production of rRFs from the 5′-end of 28S differs across several tissues.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…ª 2020 The Authors Molecular Systems Biology 16: e9275 | 2020 knowledge on the underlying mechanisms controlling tRNA expression, degradation, and the effect of their modifications will be further expanded (Pan, 2018;Rak et al, 2018). Recent studies in TCGA have actually observed an upregulation of tRNA-modifying enzymes, as well as proposed a link of tRNA-derived fragments (tRF) to proliferation (Zhang et al, 2018;Telonis et al, 2019). Overall, this is the first high-throughput study of codonanticodon translational efficiency over thousands of samples comprising multiple tissues and disease.…”
Section: Discussionmentioning
confidence: 99%